(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study sought to ascertain the opinions of business subject teachers on the strategies considered effective for teaching entrepreneurship in secondary schools in Anambra State. Two research questions and four hypotheses guided the study. Descriptive survey research design was adopted for the study. The population comprised 513 business subject teachers. A sample size of 244 business subject teachers was selected for the study using simple random sampling technique. A structured and validated questionnaire with 18 items was used for data collection. Mean was used to answer the research questions while standard deviation was used to check how close or otherwise of the respondents responses to the mean. t-test and ANOVA were used to test the hypotheses. Findings of the study revealed that the use of information and communication technology and school-industry partnership were highly effective strategies for teaching entrepreneurship. Based on the findings of the study, it was concluded that information and communication technology strategies and school industrial collaboration strategies are considered highly effective for teaching entrepreneurship. It was also concluded that gender and type of school do not affect the strategies considered effective for teaching entrepreneurship. It was recommended amongst others that, the Anambra State Government should provide funds for secondary school management, regular training and retraining programmes of business subject teachers both in public secondary schools to enable them update their ICT skills so as to utilize new technologies for instructional purposes.